Photocatalytic C−H Azolation of Arenes Using Heterogeneous Carbon Nitride in Batch and Flow. Issue 23 (22nd October 2021) - Wen, Zhenghui; Wan, Ting; Vijeta, Arjun; Casadevall, Carla; Buglioni, Laura; Reisner, Erwin; Noël, Timothy
Abstract: The functionalization of aryl C(sp 2 )−H bonds is a useful strategy for the late‐stage modification of biologically active molecules, especially for the regioselective introduction of azole heterocycles to prepare medicinally‐relevant compounds. Herein, we describe a practical photocatalytic transformation using a mesoporous carbon nitride (mpg‐CN x ) photocatalyst, which enables the efficient azolation of various arenes through direct oxidation. The method exhibits a broad substrate scope and is amenable to the late‐stage functionalization of several pharmaceuticals. Due to the heterogeneous nature and high photocatalytic stability of mpg‐CN x, the catalyst can be easily recovered and reused leading to greener and more sustainable routes, using either batch or flow processing, to prepare these important compounds of interest in pharmaceutical and agrochemical research. Abstract : Green and versatile ! The photocatalytic C(sp 2 )−H azolation of arenes using heterogeneous carbon nitride is reported. This strategy exhibits a broad substrate scope and is amenable to the late‐stage functionalization of several pharmaceuticals. The catalyst can be easily recovered and reused leading to greener and more sustainable routes.